TALENT MANAGEMENT IN FACING THE DEMAND OF ENVIRONMENTAL CHANGES: A STUDY IN GALUH UNIVERSITY - Darna, Nana; Faridah, Eva; Lestari, Marlina Nur; Tinia, Andini Grace (Sosiohumaniora, 2024)
Environmental and technological changes are unavoidable for organizations, thereby making survival dependent on the ability to adapt to the demands of these changes. This signifies a critical weakness for Galuh University, as the current lack of optimal talent management leads to a deficit in skills. Talent management has not been integrated with operational personnel activities in the procurement, placement, development, and retention of human resources (HR) resulting in inadequate skills among lecturers and education staff. Therefore, this study aims to elucidate talent management performed by Galuh University in response to environmental changes. A qualitative method was used in analyzing the actual condition of the university. Participants constituted top management of Galuh University who provided information about talent attraction, development, and retention. The results signified that talent management at Galuh University lacked proper planning, and no talent pool was available. Failure to keep pace with these changes threatens the university’s survival. HR should be optimized to anticipate environmental changes. Highly skilled personnel serve as an essential potential for organization capable of coping with environmental changes. Consequently, Galuh University is expected to execute talent management optimally.